-x=6+x+2

Simple and best practice solution for -x=6+x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x=6+x+2 equation:


Simplifying
-1x = 6 + x + 2

Reorder the terms:
-1x = 6 + 2 + x

Combine like terms: 6 + 2 = 8
-1x = 8 + x

Solving
-1x = 8 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-1x + -1x = 8 + x + -1x

Combine like terms: -1x + -1x = -2x
-2x = 8 + x + -1x

Combine like terms: x + -1x = 0
-2x = 8 + 0
-2x = 8

Divide each side by '-2'.
x = -4

Simplifying
x = -4

See similar equations:

| 5x-3=8+5y | | y+2+3y=9 | | 7(7x+8)+9=49x+65 | | 200m-100m+52800=56100-175m | | 47=6x-2 | | -15+40=6x-70 | | 200m-100m+52800=56100-175 | | 49.3x^2+33.33x-62.9=0 | | -m+16=-4(2m-4) | | 5x+3y=5.50 | | 6x+11+37+72=180 | | -3-x=-3x+x | | 6x=1+3x-1 | | 8(4s+12)=8(3s-14) | | 5-(4x^2+9x)=0 | | -4.5+n=-5 | | x+(x+2)=5 | | -10+8x=1-3x | | -3(x+5)=-2x-23 | | 6+8+x=20 | | n=160(1-.4) | | 175m-75m+52250=56375-175m | | 4m-(-m)=6-m | | -8x-17=2(-5x-6)+5 | | 3(5+7x)=30 | | 8-2x=x-4 | | 9a+20=35+4a | | A=2pirh+2pir^2 | | -2/3x=70 | | x+3+6x=9+5x | | -2x+-5=-4x+2 | | -u+74=163 |

Equations solver categories